Electrical impedance tomography to guide mechanical ventilation for asymmetrical lung injury: a case report - Musaj, Albina; Tronchet, Louis; den Uil, Corstiaan; Weller, Dolf (Frontiers in Medicine, 2025)
During last years, new methods of advanced ventilatory monitoring have been introduced to implement lung-protective ventilation. We present a unique case of a 66-year-old female admitted to the ICU with severe unilateral lung injury due to COVID-19 pneumococcal superinfection. By combining electrical impedance tomography (EIT) and esophageal pressure measurements, individualized positive end-expiratory pressure (PEEP) titration was performed. Initially, high PEEP levels (18 cmH2O) were optimal. Over the course of a week, reflecting dynamic lung recovery, PEEP levels could be reduced to 8 cmH2O followed by extubation. This case emphasizes the importance of personalized PEEP titration in managing asymmetric lung injury, highlighting how EIT-based monitoring can optimize alveolar recruitment while minimizing overdistension.